2005
DOI: 10.1002/ajh.20278
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Diamond‐Blackfan anemia with metoclopramide

Abstract: Diamond-Blackfan anemia (DBA) is a congenital anemia characterized by a low reticulocyte count, the absence or severe reduction of hemoglobin-containing cells in the bone marrow, and normal megakaryocytic and granulocytic differentiation. Although the anemia may initially respond to corticosteroid therapy, many patients require lifelong red blood cell (RBC) transfusion, leading to infectious complications and iron overload. Metoclopramide has recently been used to treat DBA. Treatment with metoclopramide induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Prolactin (PRL) has been implicated as a regulator of haematopoiesis Lowenstein 1964, 1965;Bellone et al 1997;Abkowitz et al 2002;Akiyama et al 2005). Early studies demonstrated that PRL stimulates erythropoiesis in nonpregnant, pregnant and lactating mice Lowenstein 1964, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin (PRL) has been implicated as a regulator of haematopoiesis Lowenstein 1964, 1965;Bellone et al 1997;Abkowitz et al 2002;Akiyama et al 2005). Early studies demonstrated that PRL stimulates erythropoiesis in nonpregnant, pregnant and lactating mice Lowenstein 1964, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Review ª 2008 The Authors (Totterman et al, 1984;Williams et al, 1987;Seip & Zanussi, 1988;Leonard et al, 1989;Splain & Berman, 1992;Monteserin et al, 1993;Alessandri et al, 2000;Bobey et al, 2003) or metoclopramide (Abkowitz et al, 2002;Akiyama et al, 2005;Leblanc et al, 2007), but currently these responders cannot be identified a priori. There have been two reports on the use of valproic acid (Jabr et al, 2004;Jabr & Taher, 2006) and leucine with good outcomes, however these are case reports and warrant further study before any conclusions can be drawn.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…These drugs appear to be largely ineffective and there is currently no evidence that any of these has a major role in the management of DBA (Geller et al , 1975; Dunbar et al , 1991; Fiorillo et al , 1991; Niemeyer et al , 1991; Gomez‐Almaguer & Gonzalez‐Llano, 1992;Sumimoto et al , 1992; Bejaoui et al , 1993; Gillio et al , 1993a, 1993b;Bastion et al , 1994; Brown et al , 1994; Olivieri et al , 1994; Ozsoylu, 1994; Ball et al , 1995; Bernini et al , 1995; Buchanan, 2001; Alter, 2003 ). Specific patients may respond to cyclosporine ( Totterman et al , 1984; Williams et al , 1987; Seip & Zanussi, 1988; Leonard et al , 1989; Splain & Berman, 1992; Monteserin et al , 1993; Alessandri et al , 2000; Bobey et al , 2003) or metoclopramide (Abkowitz et al , 2002; Akiyama et al , 2005; Leblanc et al , 2007), but currently these responders cannot be identified a priori . There have been two reports on the use of valproic acid (Jabr et al , 2004; Jabr & Taher, 2006) and leucine (Pospisilova et al , 2007) with good outcomes, however these are case reports and warrant further study before any conclusions can be drawn.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Unfortunately, other studies in the United States and Europe did not confirm these responses but showed an overall 10% response rate. 66,67 Most recently, leucine and lenalidomide have been contemplated for use in DBA. Recently, leucine has been tried in one patient with DBA and reported to have attained a remission.…”
Section: Alternative Therapiesmentioning
confidence: 99%